Drying characteristics of dill and parsley leaves - Doymaz, Ibrahim; Tugrul, Nurcan; Pala, Mehmet (ELSEVIER SCI LTD, 2006)
The drying of dill and parsley leaves was investigated in a laboratory dryer. The effect of temperature on drying rate of samples at constant air velocity (1.1 m/s) and various temperatures (50, 60 and 70 degrees C) was studied. Four thin-layer drying models, namely, Lewis, Handerson and Pabis, Page, and Midilli and Kucuk, were fitted to drying data. The Midilli and Kucuk model was found to satisfactorily describe the air-drying curves of dill and parsley leaves. The effective diffusivity values changed from 6.693 x 10-(10) to 1.434 x 10(-9) m(2)/s and 9.0 x 10-(10) to 2.337 x 10(-9) m(2)/s for dill and parsley leaves, respectively, within the given temperature range. Calculated values of the effective diffasivity showed Arrhenius-type temperature dependence. The activation energy values found 35.05 and 43.92 kJ/mol for dill and parsley leaves, respectively. The colour of samples were determined after drying process using a Hunterlab in terms of Hunter L*, a* and b* values. From the results of colour quality, drying in temperature of 60 degrees C was found to be the optimum temperature for dill and parsley leaves. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: parsley; dill; air-drying; colour; mathematical modelling; effective diffusivity; BEHAVIOR; KINETICS; Engineering; Food Science & Technology